Modal analysis of probe‐fed circular sector microstrip antenna with and without variable air gap: Investigation with modified cavity model. Issue 1 (7th September 2017) - Ghosh, Sudip Kumar; Chakraborty, Subhradeep; Singh, L. Lolit Kumar; Chattopadhyay, Sudipta
Abstract: Determination of accurate modal fields is one of the most crucial issues to understand the proper behavior of circular sector microstrip antennas (CSMAs) to achieve the best performance. In this article, dominant and higher order modal characteristics have been rigorously studied which germinate an improved, accurate, and efficient computer‐aided design (CAD) formulation to estimate the resonant frequency of CSMA with and without air gap between substrate and ground plane. The proposed formulation can address the wide variety of issues (such as substrate height, substrate permittivity, air gap height, higher order modes, etc.). The computed results were validated against the results obtained from high‐ frequency structure simulator (HFSS) and our own experiments, while they have been also justified through the results obtained from the available literature.